2018
DOI: 10.3391/mbi.2018.9.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of carbon dioxide as a fish deterrent at a water management structure along the Illinois River

Abstract: Management of invasive species, whether prevention, population reduction, or eradication, requires assessment of the invasive species' population status and an assessment of the probability of success of management options. Perceptions of a species' permanence in an environment or lack thereof frequently drives how limited time, financial, and personnel resources are allocated to such efforts. Language we use to describe a non-native species' status largely defines these perceptions and sets boundaries, real o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…The success of these laboratory trials led to work at larger settings, including Donaldson et al [86] who showed that a number of fish species, including silver carp and bigheaded carp, released into a 4000 m 3 outdoor pond in groups of 5-10 avoided zones of elevated CO 2 elevated to approximately 30,000 µatm (60 mg/L), and Cupp et al [87] who used a two-channel, outdoor raceway (approximately 60 m 3 ) with flowing water and showed that CO 2 levels of approximately 30,000-40,000 µatm (~75 mg/L) would deter the movement of both silver and bigheaded carp (278 mm and 212 mm, respectively) when tested in groups of 10 (Table 1). Cupp et al [88] showed that CO 2 deployed at the mouth of an outflow structure draining a backwater lake could reduce the abundance of shoals of mixed fish species by 70-95% at low water flows once a target threshold of 100 mg/L was reached. Finally, Hasler et al [89] worked in a 12 m long indoor swim flume and showed that bighead carp (145 mm) in shoals of 3 would avoid CO 2 in water flowing at approximately 15 cm/seconds (equivalent to 1 body length per second), and CO 2 levels in this study were approximately 190,000 µatm.…”
Section: Co 2 and Physiological Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of these laboratory trials led to work at larger settings, including Donaldson et al [86] who showed that a number of fish species, including silver carp and bigheaded carp, released into a 4000 m 3 outdoor pond in groups of 5-10 avoided zones of elevated CO 2 elevated to approximately 30,000 µatm (60 mg/L), and Cupp et al [87] who used a two-channel, outdoor raceway (approximately 60 m 3 ) with flowing water and showed that CO 2 levels of approximately 30,000-40,000 µatm (~75 mg/L) would deter the movement of both silver and bigheaded carp (278 mm and 212 mm, respectively) when tested in groups of 10 (Table 1). Cupp et al [88] showed that CO 2 deployed at the mouth of an outflow structure draining a backwater lake could reduce the abundance of shoals of mixed fish species by 70-95% at low water flows once a target threshold of 100 mg/L was reached. Finally, Hasler et al [89] worked in a 12 m long indoor swim flume and showed that bighead carp (145 mm) in shoals of 3 would avoid CO 2 in water flowing at approximately 15 cm/seconds (equivalent to 1 body length per second), and CO 2 levels in this study were approximately 190,000 µatm.…”
Section: Co 2 and Physiological Responsesmentioning
confidence: 99%
“…Fishes 2020, 5, x FOR PEER REVIEW 8 of 21 30,000-40,000 µ atm (~75 mg/L) would deter the movement of both silver and bigheaded carp (278 mm and 212 mm, respectively) when tested in groups of 10 (Table 1). Cupp et al [88] showed that CO2 deployed at the mouth of an outflow structure draining a backwater lake could reduce the abundance of shoals of mixed fish species by 70-95% at low water flows once a target threshold of 100 mg/L was reached. Finally, Hasler et al [89] worked in a 12 m long indoor swim flume and showed that bighead carp (145 mm) in shoals of 3 would avoid CO2 in water flowing at approximately 15 cm/seconds (equivalent to 1 body length per second), and CO2 levels in this study were approximately 190,000 µ atm.…”
Section: Co 2 and Physiological Responsesmentioning
confidence: 99%
“…Further testing using telemetered Asian carps over larger spatial scales in outdoor ponds found similar positive results (Cupp et al 2018b). When administered into static water, CO 2 at approximately 60 mg/L excluded fish from certain locations (Donaldson et al 2016).…”
Section: Carbon Dioxidementioning
confidence: 79%
“…The present study showed that CO 2 can generally induce widespread loss of equilibrium at approximately 118 to 160 mg/L CO 2 for bluegill and 274 to 398 mg/L CO 2 for fathead minnow. Previous studies have concluded that CO 2 is an effective deterrent for invasive carps at generally modest concentrations (e.g., 50–150 mg/L CO 2 ), and it is not likely that widespread loss of equilibrium across all species would occur at these levels (Cupp et al 2017a, 2017b, 2018a; Tix et al 2018). However, applications for lethal purposes that use higher CO 2 concentrations may induce loss of equilibrium, which could mitigate the potential for individuals to avoid lethal exposure.…”
Section: Discussionmentioning
confidence: 99%